(untitled) (Economic and Political Thought, 2015)
The article presents a theoretical analysis of a command economy from a historical perspective. Presenting the Soviet system, the author refers to the Marxist-Leninist-Stalinist heritage. This is the spirit of the author’s analysis of the system limited by demand or available resources and a discussion of the forms of property and the methods of co-ordination used in the command system as well as the specific system of budget development. At the same time, the author emphasises that there is a lack of theoretical analyses of the then used economic system as they were not conducted at that time, and thus there are no indicators that would make it possible to lay down guidelines on reforming such a system.